THE ANALYSIS OF LANGUAGE STYLE USED IN MERRY RIANA’S YOUTUBE CHANNEL ON THE PLAYLIST ‘SPOKEN WORD’ - Ester Febrina Br Sitepu; Ayuna Zahara; Ardhia Amalya Cahyani Putri; Rahmadsyah Rangkuti (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2023)
The aim of this study was to find out the types of language styles and identify the dominant style of language used by Merry Riana in her selected motivational speech videos as a motivator. The data of this study were taken from Merry Riana’s YouTube Channel and the researchers chose 3 motivational speech videos in the "SPOKEN WORD" playlist. In analyzing the data, the researchers used descriptive qualitative method. The researchers used the theory proposed by Martin Joss (1967) to identify the types of language styles. According to Martin Joss (1967), there are five language styles: frozen style, formal style, casual style, consultative style, and intimate style. The researchers found that in Merry Riana’s motivational speech used three language styles from five language styles proposed by Martin Joss. There were 64 formal styles, 42 casual styles, and 4 intimate styles from the 117 sentences uttered by the speaker in the selected video. The most dominant style of language found in this study was the formal style.